From the underground church to freedom - Halík, Tomáš (University of Notre Dame Press, 2019)
"International best-selling author and theologian Tomas Halik shares for the first time the dramatic story of his life as a secretly ordained priest in Communist Czechoslovakia. Inspired by Augustine's candid presentation of his own life, Halik writes about his spiritual journey within a framework of philosophical theology; his work has been compared to that of C.S. Lewis, Thomas Merton, and Henri Nouwen. Born in Prague in 1948, Halik spent his childhood under Stalinism. He describes his conversion to Christianity during the time of communist persecution of the church, his secret study of theology, and secret priesthood ordination in East Germany (even his mother was not allowed to know that her son was a priest). Halik speaks candidly of his doubts and crises of faith as well as of his conflicts within the church. He worked as a psychotherapist for over a decade and, at the same time, was active in the underground church and in the dissident movement with the legendary Cardinal Tomasek and Vaclav Havel, who proposed Halik as his successor to the Czech presidency. Since the fall of the regime, Halik has served as general secretary to the Czech Conference of Bishops and was an advisor to John Paul II and Vaclav Havel. Woven throughout Halik's story is the turbulent history of the church and society in the heart of Europe: the 1968 Prague Spring, the occupation of Czechoslovakia, the self-immolation of his classmate Jan Palach, the "flying university," the 1989 Velvet Revolution, and the difficult transition from totalitarian communist regime to democracy. Thomas Halik was a direct witness to many of these events, and he provides valuable testimony about the backdrop of political events and personal memories of the key figures of that time"-- Provided by publisher.
Translation of: To že byl život? : z podzemní církve do labyrintu svobody.
Keywords: Halík, Tomáš.; Catholic Church -- Czech Republic -- Clergy -- Biography.; Catholic Church -- Clergy -- Biography.; Église catholique -- Clergé -- Biographies.; Halík, Tomáš; Catholic Church; Theologians -- Czech Republic -- Biography.; Intellectuals -- Czech Republic -- Biography.; Czechoslovakia -- Politics and government -- 1968-1989.; Czechoslovakia -- Church history.; Théologiens -- République tchèque -- Biographies.; Intellectuels -- République tchèque -- Biographies.; Tchécoslovaquie -- Politique et gouvernement -- 1968-1989.; BIOGRAPHY & AUTOBIOGRAPHY / Religious; Clergy; Intellectuals; Politics and government; Theologians; Czech Republic; Czechoslovakia; 1968-1989; Biographies; Church history